The Influence of Workload, Work Motivation, and Physical Work Environment on Employee Performance - Fitriyani, Indah; Krisnandi, Herry; Digdowiseiso, Kumba (International Journal of Social Service and Research, 2024)
This study investigates the impact of workload, work motivation, and the physical work environment on employee performance within the Finance and Equipment Section of the Secretariat of the Directorate General of Livestock and Animal Health, Ministry of Agriculture. The population comprises 150 employees within this section. Utilizing the Slovin formula, a sample of 110 employees was selected. Data analysis was conducted using SPSS version 23, employing multiple linear regression. The results revealed significant findings supporting the three hypotheses proposed. However, the abstract does not provide specific details about the magnitude and direction of these effects. The study suggests that the Finance and Equipment Division employees can enhance their performance by addressing factors such as workload, work motivation, and the physical work environment. Practical implications and recommendations for implementation are not explicitly mentioned in the current abstract. In summary, while the abstract effectively outlines the study's objectives and methodology, it could benefit from greater specificity, conciseness, and clarity in presenting the essential findings and their practical implications.